Current Issues Related to Athlete Motivation in the Perspective of Literature Review - Sin, Tjung Hauw; Sari, Suci Nanda; Susanto, Eko (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2021)
Recent studies on athlete motivation have been widely carried out in the last five years. Almost all studies identify subjects that can influence athlete motivation. The purpose of the study in this article was to obtain significant information related to the research topic "athlete motivation". The study design used is a systematic review. The reference data collection was collected in the last five years (2017-2022). Data interpretation was carried out based on the results of the exploration of the 78 selected articles. The results of this study obtain related information; (1) the issue of intervention related to the development of athlete motivation, (2) gender issue related to the motivational differentiation of male and female athletes. And (3) other external issues that affect athlete motivation.Keywords: athlete motivation; intervention; gender; literature review AbstrakStudi terkini tentang motivasi atlet sudah banyak dilakukan dalam kurun waktu lima tahun terakhir. Hampir semua studi mengidentifikasi subjek yang dapat mempengaruhi motivasi atlet. Tujuan studi pada artikel ini dilakukan untuk mendapatkan informasi signifikan terkait topik penelitian “motivasi atlet”. Desain studi yang digunakan adalah systematic review. Koleksi data referensi dikumpulkan dalam kurun waktu lima tahun terakhir (2017-2022). Interpretasi data dilakukan berdasarkan hasil eksplorasi dari 78 artikel yang terpilih. Hasil studi ini memperoleh informasi terkait; (1) isu intervansi terkait pembinaan motivasi atlet, (2) isu gender terkait diferensiasi motivasi atlet laki-laki dan perempuan. Dan (3) isu-isu eksternal lainnya yang mempengaruhi motivasi atlet.Kata kunci: motivasi atlet; intervensi; gender; literatur review